Epistomologi Kebenaran Terhadap Hukum - Pandri Zulfikar (JUNCTO: Jurnal Ilmiah Hukum, 2022)
This article aims to find the truth of the law epistemologically, Epistomology has an exploration in the scope of how knowledge can basically be obtained and tested for truth, if it is specified in the realm of legal epistemology, the study is in an effort to listen to how legal knowledge can be obtained and how level of truth so that it can be a determinant of legal methodology. The meaning of truth according to the Big Indonesian Dictionary is the real situation. Truth is "absolutely true", even though it is actually a reconstructive truth. Legal truth is coherent truth, The Accordance Theory of Truth. This theory explains that a truth or a condition is true if there is a match between the intended meaning of a statement or opinion with the object intended or intended by the statement or opinion. Truth in the Law of Evidence In each definition of the law of evidence there are six things that will be discussed further regarding the parameters of the law of proof, each of which is bewijstheorie, bewijsmiddelen, bewijsvoering, bewijslast, bewijskracht, and minimum bewijs. The type of research used in this research is qualitative, normative juridical research type. Legal materials are analyzed qualitatively by explaining theories, logical principles to obtain scientific results that are descriptive. The epistemology of legal science can be accommodated into a single unit in a meeting point of legal truth. The concept of convergence of legal epistemology seeks to open and dilute the pattern of relationships that are independent and mutually dominate legal truth, with this concept legal truth does not come from one legal thought alone, but can be extracted from all legal epistemologies in Indonesia, so that with this concept the truth the resulting law is more complete and comprehensive. The truth of the law, using pragmatic theory, the truth of the law is related to the usefulness of the law. The pragmatic truth perspective is not oriented to a process or a legal event but the result of the legal process or event. Something is said to be true if it has benefits for human life. What is felt useful is the real law.